Peran Organisasi Santri Husada (Sanhus) terhadap Efektivitas Pembelajaran di Lingkungan Pesantren Putri Tebuireng - Fitria Mauilida; Khoirul Anwar; pengelola, pengelola (STAI Ihyaul Ulum Gresik, 2023)
To maintain the cleanliness of the Islamic boarding school environment, the role of students/students in it is needed to achieve a clean and healthy environment, but most students still don't want to play a role in it, such as sometimes throwing rubbish in their rooms, not carrying out room pickets and not maintaining and caring for the environment properly. Therefore, to ensure a clean and healthy learning environment, the Tebuireng Islamic Boarding School created the Santri Husada Organization (SANHUS). Within this organization, of course, many programs are designed. This research wants to find out the duties and roles of Santri Husada regarding the effectiveness of learning in the Putri Tebuireng Islamic Boarding School environment. This research is qualitative research that focuses on the phenomenon of the Santri Husada Organization (SANHUS), such as the behavior and motivation of members. Carried out using field research methods with researchers working directly at the Tebuireng Islamic Boarding School, Jombang. Descriptive methods were used to comprehensively describe the SANHUS situation. The results of this research are that the Santri Husada Organization (SANHUS) plays a significant role in helping condition and train santri hygiene and health habits. With the existence of the Santri Husada Organization (SANHUS) at the Tebuireng Islamic Boarding School for Girls, learning is felt to be quite effective. Because it can help maintain cleanliness and health in Islamic boarding schools so that learning runs effectively.